Cashless gambling and the pain of paying: effects of monetary format on slot machine gambling. (4th May 2022) - Limbrick-Oldfield, Eve H.; Chua, Candy; Cringle, Natalie; MacDonald, Kent; Ferrari, Mario A.; Zhang, Ke; Clark, Luke
Abstract: Advances in cashless technologies create a dilemma for gambling regulators. Research indicates that cash purchases entail a 'pain of paying' that is attenuated with more abstract forms of payment, yet limited research has directly tested the impact of mode of payment on gambling behavior. Across two experiments, community-recruited gamblers were randomized to use an authentic slot machine in the laboratory, under different conditions of monetary endowment. In Experiment 1 (n = 61), participants were endowed with funds to play the slot machine, in either a cash or voucher format. In Experiment 2 (n = 48), participants acquired the cash endowment as a windfall or from an earning task. In session-level analyses, bet size and bet volume did not vary as a function of monetary condition. In more sensitive trial-level analyses, no interactions involving the monetary manipulations were consistent across the two experiments. Data from both experiments indicated faster spin initiation latencies as a function of losing streak length, and slower spin initiation latencies and larger bet size as a function of the prior win magnitude. These trial-level analyses show systematic influences on gambling behavior in the laboratory environment, supporting the basic sensitivity of our design. Overall, our data provide weak evidence for the hypothesis that monetary factors influence gambling tendencies. Acknowledging the possibility of the null hypothesis, these data also highlight the methodological challenges with manipulating monetary value in gambling research, including the use of endowed funds, and controlling for sources of variability when using authentic slot machines.